Hemodynamic evaluation of pulsatile-flow generating device in left ventricular assist devices - A. S. Buchnev; A. P. Kuleshov; O. Yu. Esipova; A. A. Drobyshev; N. V. Grudinin (Вестник трансплантологии и искусственных органов)
Objective: to investigate the efficiency of a device that generates pulsatile flow during constant-speed axial-flow pump operation for use in left ventricular assist devices.Materials and methods. The pulsatile flow-generating device, hereinafter referred to as «pulsator», consists of a variable hydraulic resistance made in the form of a hull. A tube of elastic biocompatible material featuring an inner diameter of 11 mm is installed inside it. In the systolic phase of the left ventricle, due to systolic pressure, the elastic tube is fully opened, minimizing resistance to blood ejection. In the diastolic phase, due to suction action of the flow pump operating in constant revolutions, the elastic tube partially closes, creating additional hydraulic resistance to blood flow, which leads to reduced diastolic aortic pressure. Comparative assessment of axial-flow pump operation in pulsating and non-pulsating modes was carried out on a hydrodynamic stand that simulated the cardiovascular system. The following indices were calculated: arterial pressure pulsation (Ip), in-pump flow pulsation (AQ), energy equivalent pressure (EEP) and surplus hemodynamic energy (SHE).Results. When comparing axial-flow pump operation in pulsatile and continuous mode, arterial pressure pulsation index, in-pump pulsation index, and SHE index increased by 2.13 ± 0.2, 3.2 ± 0.2, and 2.7 ± 0.15 times, respectively, while EER index remained unchanged.